Peptide-Based Inhibitors of ADAM and ADAMTS Metalloproteinases - Pluda, Stefano; Mazzocato, Ylenia; Angelini, Alessandro (Frontiers in Molecular Biosciences, 2021)
ADAM and ADAMTS are two large metalloproteinase families involved in numerous physiological processes, such as shedding of cell-surface protein ectodomains and extra-cellular matrix remodelling. Aberrant expression or dysregulation of ADAMs and ADAMTSs activity has been linked to several pathologies including cancer, inflammatory, neurodegenerative and cardiovascular diseases. Inhibition of ADAM and ADAMTS metalloproteinases have been attempted using various small molecules and protein-based therapeutics, each with their advantages and disadvantages. While most of these molecular formats have already been described in detail elsewhere, this mini review focuses solely on peptide-based inhibitors, an emerging class of therapeutic molecules recently applied against some ADAM and ADAMTS members. We describe both linear and cyclic peptide-based inhibitors which have been developed using different approaches ranging from traditional medicinal chemistry and rational design strategies to novel combinatorial peptide-display technologies.